2022
DOI: 10.1039/d1ra09116f
|View full text |Cite
|
Sign up to set email alerts
|

Electronic energy levels of porphyrins are influenced by the local chemical environment

Abstract: Self-assembled islands of 5,10,15,20-tetrakis(pentafluoro-phenyl)porphyrin (2HTFPP) on Au(111) contain two bistable molecular species that differ by shifted electronic energy levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Before azobenzene deposition, the gold sample was imaged under the STM to ensure proper surface cleaning. A ~1 mM solution of 4‐(phenylazo)benzoic acid (PABA) dissolved in chloroform was deposited on the clean Au surface using a pulsed‐solenoid valve in the vacuum chamber [24,68,69] . Gentle annealing of the sample was carried out at 343 K to remove excess solvent and study the effects of different molecular packing on the surface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before azobenzene deposition, the gold sample was imaged under the STM to ensure proper surface cleaning. A ~1 mM solution of 4‐(phenylazo)benzoic acid (PABA) dissolved in chloroform was deposited on the clean Au surface using a pulsed‐solenoid valve in the vacuum chamber [24,68,69] . Gentle annealing of the sample was carried out at 343 K to remove excess solvent and study the effects of different molecular packing on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…A.03 [73] . Simulated STM images were computed using the Tersoff Hamman approximation as done in prior papers [68,69,74–78] . The tip was modeled as an s‐orbital and the surface as featureless and having a constant density of states to reproduce a constant current experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 STM images were simulated using the Tersoff and Hamann approximation 40,41 as done previously. 36,42,43 Molecular manipulation experiments were performed to determine the flexibility of the COFs and to corroborate that the molecules were covalently coupled. The pulse deposition of TBrPP leads to the formation of selfassembled porphyrin islands.…”
Section: Methodsmentioning
confidence: 99%
“…35 Moreover, recent studies have demonstrated that the Au(111) herringbone affects the electronic states of a TFPP porphyrin, leading to the formation of two equivalent conformations of the molecule with shifted electronic states. 36 Therefore, investigating the interplay between the underlying Au(111) substrate and its role in the electronic structure and chemical properties of porphyrins is crucial for further understanding. Here, the Au(111) herringbone plays a role in the self-assembly and on-surface metalation of a pulse-deposited solution of TBrPP.…”
Section: Introductionmentioning
confidence: 99%